Antimicrobial and Odour Qualities of Alkylpyrazines Occurring in Chocolate and Cocoa Products - Alina Cherniienko; Anna Pawełczyk; Lucjusz Zaprutko (Applied Sciences, 2022)
A total of 40 pyrazine compounds of cocoa and chocolate were discovered through a literature analysis. Data on the alkylpyrazines’ antibacterial properties were gathered. It was discovered that 12 substances were effective against bacteria, fungus and oomycetes. Following calculations using PASS and AntiBac-Pred, 15 substances were identified as potentially having the ability to inhibit the growth of the Picornavirus, Yersinia pestis, Resistant Mycobacterium tuberculosis, Mycobacterium bovis BCG (Bacillus Calmette-Guerin), Micrococcus luteus and Corynebacterium jeikeium. The study of odour qualities led to the identification of the most potent odourants among alkylpyrazines as well as the aroma composition of cocoa and chocolate. Pyrazines have been given GRAS (generally recognized as safe) status by the Flavor and Extract Manufacturers Association (FEMA) for use as flavouring additives in food, demonstrating that this class of chemicals is a secure substitute for managing and combating microbial contamination, which also provides beneficial odour properties to the recipient. A statistical evaluation of the correlation between the odour threshold and the probability of antibacterial activity was performed. A more in-depth investigation of the antimicrobial and olfactory activities of alkylpyrazines is required in the future.